Microbial alterations in the lungs of children with chronic pulmonary aspiration - Freitag, Nadine; Wienemann, Tobias; Nguyen, Thi Minh Thao Lea; Höhn, Thomas; Kristin, Julia; Schramm, Dirk (Frontiers in Pediatrics, 2025)
IntroductionChronic pulmonary aspiration (CPA), a common complication of pediatric dysphagia, poses significant risks to respiratory health, potentially leading to bronchiectasis and permanent lung damage. Despite its clinical impact, the mechanisms underlying aspiration-related lung injury remain unclear. This study investigates the microbial alterations in the lungs of children with CPA and their association with immune responses.MethodsWe conducted a retrospective analysis of bronchoalveolar lavage fluid (BALF) from children diagnosed with CPA and from controls without swallowing difficulties. Data were collected from patients who underwent bronchoscopy at the University Hospital Düsseldorf between 2010 and 2022. Microbial profiles—including bacterial, viral, and fungal components—and immune cell populations, were assessed to explore the relationship between microbial colonization and immune response in CPA.ResultsThe study included 371 children, of whom 48 had CPA. The CPA group exhibited altered microbial colonization, with an increased prevalence of Pseudomonas aeruginosa and Enterobacterales. While the presence of mixed upper respiratory flora did not differ significantly between groups, pathogenic bacteria were more frequently detected in CPA patients. Notably, total leukocyte counts were elevated in the CPA group, yet neutrophilia was absent.DiscussionOur findings suggest that children with CPA have a distinct lung microbial composition, characterized by increased colonization of Enterobacterales and P. aeruginosa. These microbial changes may contribute to the pathogenesis of aspiration-related lung disease. Further research is needed to determine whether microbial colonization directly contributes to lung damage in and assess long-term consequences.ConclusionMicrobial dysbiosis in the lungs of children with CPA underscores the need for targeted interventions to prevent or mitigate aspiration-related lung disease. A deeper understanding of microbial colonization in CPA may pave the way for novel therapeutic strategies and improved patient outcomes.